Improved hydrogen evolution activity of layered double hydroxide by optimizing the electronic structure - Feng, Haopeng; Yu, Jiangfang; Tang, Lin; Wang, Jiajia; Dong, Haoran; Ni, Ting; Tang, Jing; Tang, Wangwang; Zhu, Xu; Liang, Chao (Applied catalysis. B, Environmental, 2021)
[Display omitted] •P doping can weaken MO bonds by forming PO bonds.•The deposition of metal nanodots can destabilize water molecules.•This strategy can effectively improve Volmer and Heyrovsky process of HER catalysis.•The mechanism of enhanced HER activity is well explained. The layered double hydroxides (LDHs) are considered to own great potential to serve as a catalyst for water electrolysis, while their extremely poor hydrogen evolution reaction (HER) activity limits their application. Herein, a general designing strategy to improve the HER activity of LDHs by P doping and deposition of metal nanodots (NDs) is proposed, which increases one order of magnitude higher than that of pristine LDHs. The obtained electrocatalyst, such as Cu NDs/P-FeCoLDH (CPFC-LDH), reaching a current density of 10 mA/cm2 with only 63 mV overpotential for HER in alkaline electrolyte. The adsorption energy of Hads and OH on catalyst is optimized by this strategy, which can weaken the interaction between the adsorbed Hads and electronegative oxygen in LDHs by formation of PO bonds. This work provides a strategy to develop LDHs materials with high catalytic activity for HER.